2023
DOI: 10.21315/mjms2023.30.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parental Role in Children’s Participation in Decision Making during Hospitalisation: An Ethnographic Study in Malaysia

Abstract: Introduction: Despite a growing recognition internationally that children have a right to participate in matters that affect their lives, they are not always involved in decision-making processes concerning their health care. There is a lack of information on how parents influence children’s participation in this decision making. This study explored the roles parents assume in processes regarding their children’s participation in communication exchanges and decision making in a paediatric oncology unit in Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…I read the insightful article entitled ‘Understanding parental role in children’s participation in decision making during hospitalisation: An ethnographic study in Malaysia’ by Lee et al ( 1 ) with considerable interest. While this study has identified three fundamental parental communication functions during children’s hospitalisation, for this commentary, I would like to focus on how parents have embraced the role of an interpreter.…”
mentioning
confidence: 99%
“…I read the insightful article entitled ‘Understanding parental role in children’s participation in decision making during hospitalisation: An ethnographic study in Malaysia’ by Lee et al ( 1 ) with considerable interest. While this study has identified three fundamental parental communication functions during children’s hospitalisation, for this commentary, I would like to focus on how parents have embraced the role of an interpreter.…”
mentioning
confidence: 99%